2021
DOI: 10.1021/acs.orglett.1c00487
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of 9,10-Dihydroacridines through an ortho-C Alkenylation/Hydroarylation Sequence between Anilines and Aryl Alkynes in Hexafluoroisopropanol

Abstract: 9,10-Dihydroacridines are frequently encountered as key scaffolds in OLEDs. Yet, accessing those compounds from feedstock precursors typically requires multiple steps. Herein, a modular one-pot synthesis of 9,10-dihydroacridine frameworks is achieved through a reaction sequence featuring a selective ortho-C alkenylation of diarylamines with aryl alkynes followed by an intramolecular hydroarylation of the olefin formed as intermediate. This transformation was accomplished by virtue of the combination of hexaflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…Compounds 5b – l were synthesized for the first time in this study. The first synthesis of 5a was prepared by reduction of the corresponding xanthydrol [ 53 ] and was also synthesized recently by a different method from our group [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 5b – l were synthesized for the first time in this study. The first synthesis of 5a was prepared by reduction of the corresponding xanthydrol [ 53 ] and was also synthesized recently by a different method from our group [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some other new and prominent synthesis methods of xanthenes are the tandem arylation/Friedel–Crafts reaction of o -hydroxy bisbenzylic alcohols with diaryliodonium salts [ 26 ], the Sc(OTf) 3 -catalyzed domino reaction [ 27 ], and the iodine-catalyzed nucleophilic substitution reaction of xanthen-9-ol [ 28 ]. As an example of an intramolecular hydroarylation of an olefin, 9,10-dihydroacridines, which are N derivatives of xanthenes, were synthesized using the combination of hexafluoroisopropanol and triflimide as a catalyst [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, {RuCl 2 (pcymene)} 2 and AgSbF 6 were applied as cocatalysts to promote the reaction of substituted N -phenylacetamides with 1-(prop-1-ynyl)­benzene to give ortho substituted aniline derivatives (Figure b) . Very recently, Leboeuf et al reported that HNTf 2 could catalyze ortho -alkenylation of diarylamines with alkynes followed by the intramolecular hydroarylation (Figure c) . On the basis of our continuous efforts in exploring chemical transformations of ynamides, we envisioned that transition-metal salts (as Lewis acids) could catalyze the C–H activation of tertiary arylamines with ynamides, i.e., the hydroarylation of ynamides.…”
Section: Introductionmentioning
confidence: 99%
“…In hexafluoroisopropanol (HFIP), a solvent known for its H-bond donating ability, the strength of catalytic Brønsted acids is drastically increased, rendering electronically deactivated substrates more reactive . We recently reported an efficient, practical, and broadly applicable Friedel–Crafts arylation of epoxides, including highly deactivated styrene oxides, using catalytic triflic acid (TfOH) in HFIP. , The formed alcohols could undergo a second arylation to access diaryl- and triarylalkanes without preactivation, although this is less efficient when two different nucleophiles were employed.…”
mentioning
confidence: 99%